(untitled) (International Journal of Food and Nutritional Sciences, 2020)
Japanese Encephalitis, Known as “Plague of the Orient” is an important-emerging vector-borne zoonotic diesese of the 21stCentury.The objective are to access the level of knowledge regarding Japanese Encephalitis and its prevention among students and To evaluate the effectiveness of an information booklet regarding Japanese Encephalitis and its prevention among students and To find out the association between knowledge score with their selected demographic variables of students in selected senior secondary school at Kanpur UP.A Quasi experimental one group pre- test post- test design with 60 senior secondary school students were selected by simple random sampling technique and data collection done by self-structured questionnaire regarding senior secondary school students.The mean score of post-test knowledge 28.31 (60.73%) was apparently higher than the mean score of pre-test knowledge 12 (41.86%), suggesting that the information booklet was effective in increasing the knowledge of the senior secondary school students regarding Japanese encephalitis and its prevention. The mean difference 16.31 between pre-test and post-test knowledge score of the senior secondary school students were found to be significant and there was no association between pre-test knowledge score and demographic variables among students of senior secondary school regarding Japanese encephalitis and its prevention.